Do the Government Support Salt Small and Medium Enterprises’ Competitiveness? - Asep Saefuddin; Rahmadi Sunoko; Rizal Syarief; Nimmi Zulbainarni (Bina Nusantara University, 2023)
As a strategic commodity, salt in Indonesia faces the challenges of increasing imports rather than the capacity to produce locally, which SMEs almost produce. Therefore, the research explored the extent of the government’s role in the competitiveness of salt SMEs. The research applied a descriptive method with a qualitative approach. For policy analysis, literature review, observation, and in-depth interviews were conducted to analyze the effectiveness of government policies using Regulatory Impact Assessment (RIA) and Cost-Benefit Analysis (CBA). The results find that at least six issues on the existing policies need concern. It consists of local people who are allowed to produce salt, the President Decree 69/1994 role and position, the salt consumption, which is mandatory to have SNI, the changeable salt classification, the other SNI than voluntary iodized consumption salt, and SNI for food-grade salt and caustic soda (chlor-alkali products). The situation shows the government’s significant role in influencing the competitiveness of sustainable salt SMEs. Subsequently, the research proposes recommendations for the sustainable competitiveness of Small and Medium Enterprises (SMEs) on salt industry development, such as arranging new regulations or revising the existing regulation by integrating and harmonizing the interest cross-ministries, establishing the task force under the Coordinating Ministry for Economic Affairs or directly under the president to prepare the national salt industries development. The national salt classification needs to be considered as the applicable classification internationally. Salt is salt, so there is no need to differentiate it into local and imported salt. Therefore, the imported salt can be classified into food-grade and Chlor-Alkali products (CAP) salt, which should meet international standards and be mandatory.